Pengaruh Debt to Equity Ratio, Total Assets Turnover, Firm Size, dan Net Profit Margin terhadap Return on Assets - Citra Dewi Damayanti; Eko Hariyanto; Azmi Fitriati; Edi Joko Setyadi (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
Financial performance is the main indicator for assessing a company's effectiveness in managing and utilizing financial resources to achieve predetermined operational goals. Financial performance evaluation is generally conducted using financial ratio analysis as a relevant measuring tool. This study aims to examine the effect of Debt to Equity Ratio (DER), Total Asset Turnover (TATO), Firm Size, and Net Profit Margin (NPM) on Return on Assets (ROA) in companies operating in the food and beverage subsector during the period 2020 to 2023. The sampling method used a purposive sampling technique with a sample size of 154 observational data that met the research criteria. Data analysis was conducted using a multiple linear regression approach. The results show that the TATO and Firm Size variables have a positive and significant effect on ROA, indicating that the higher the asset turnover and company size, the greater the resulting profitability. Conversely, the DER and NPM variables did not show any effect on ROA in this study.